Research on the Translation of Indirect Expressive Speech Acts Identified in the Novel It Ends With Us - Salsabila, Khoirunnisa (Universitas Sebelas Maret, 2023)
This study aims to find all indirect expressive speech acts in the It End With Us novel, classify them, examine if they underwent a shift in the translation, and assessed the quality of the translation. This is a descriptive qualitative research and used purposive sampling technique. The data were later analyzed using content analysis method and were verified in Focus Group Discussion. It was discovered that this novel contained 33 indirect expressive speech acts with the following classification: boasting (10), deploring (8), complimenting (5), lamenting (5), forgiving (2), condoling (1), thanking (1), and apologizing (1). No data underwent a shift in indirectness. It can be concluded that the difficulty of translating indirect expressive speech acts is affected by several factors such as the cultural disparity between the source and target language, finding the equivalent words in the target language, and the minimum understanding on the context of the work. Additionally, the score for accuracy and acceptability is 2,81 and 2,55, while the final score of the Translation Quality Assessment is 2,68, indicating that despite the translation being imperfect, the translator has overall successfully translated the indirect expressive speech acts into the target language.